Knowledge and attitudes of Peruvian women on Climacteric and Menopause - Pacheco Romero, José (2015)
OBJECTIVES: To establish knowledge of Peruvian women on climacteric and menopause and their attitude towards hormonal therapy. DESIGN: Transversal, descriptive study based on a survey in different regions of Peru. SUBJECTS: Women over 39 years old. RESULTS: High parity, stable union dependent, housewife, and low grade of education were found. Fifty-four percent of patients define menopause by absence of periods, 51,8% by presence of symptoms, and 47,3% do not identify the cause; 86% know symptomatology, specially hot flushes and neuropsychiatric symtions, and 67,3% present them; 70,5% know about treatment, only 14,9% receive it, 90% wish to receive it, but only 57,3% would accept hormones; 38,2% are afraid of hormones and 69,5% are afraid to conceive if vaginal bleeding returns; 75,6% believe government participation is necessary and 68,7% wish more information on hormonal replacement therapy benefits. Most women think physical exercise, low salt and fat ingestion, and no smoking are important, but only 17,5% drink milk occasionally. CONCLUSION: The need to give information on menopause and its treatment to Peruvian women and the eventual government participation in this important aspect are emphasized.